Prevalence of sleep disorders among medical students of Umm Al-Qura University, Makkah, Kingdom of Saudi Arabia - Reda Abdelmoaty Goweda; Abdurahman Hassan-Hussein; Mohammed Ali Alqahtani; Murad Mohammed Janaini; Adi Hatim Alzahrani; Basil Mamdooh Sindy; Moayad Mansour Alharbi; Sari Abdulhamid Kalantan (SAGE Publishing, 2021)
Background: Sleep disorders are a common medical problem and can affect health and quality of life. There are multiple types of sleep disorders such as obstructive sleep apnea, insomnia, narcolepsy, restless legs/periodic limb movement disorder, circadian rhythm disorders, sleepwalking and nightmares. Medical students appear to be more liable to develop sleep disorders due to their high academic load. Design and Methods: This study seeks to estimate the prevalence of sleep disorders among Umm Al-Qura University medical students and associated risk factors. This cross-sectional study was conducted at the Faculty of Medicine of Umm Al-Qura University in Makkah, Saudi Arabia. A self administrated questionnaire was used to collect the data including socio-demographic data and sleep-50 questionnaire. Four hundred and thirty-eight (438) medical students from the second year to the sixth year were recruited to the study. Results: Three hundred and twenty-three participants (73.8%) complained of at least one sleep disorder. The most prevalent sleep disorder among students was narcolepsy at 226 (51.6%). Female students, second year students and students spending significant time watching television or on smartphones were more affected than others with p values of 0.001, 0.005, and 0.004, respectively. Conclusions: Sleep disorders are common among medical students. It is essential to detect and address them before their condition deteriorates.